Pengaruh Kompres Hangat Terhadap Tingkat Nyeri Punggung Bawah Pada Ibu Hamil Trimester III - Tati Karyawati; Yusriani Saleh; Nurhidayati Nurhidayati; Iin Nur Aeni (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Background: Lower back pain is one of the complaints felt by almost all pregnant women, especially in the third trimester due to stretching, especially in the spine due to the enlargement of the uterus. Efforts to reduce back pain in pregnant women non-pharmacologically include warm compresses. The aim of the research was to determine the effect of warm compresses on the level of lower back pain in third trimester pregnant women. Method: This research uses a pre-experiment method with a research design using one group pre test post test. The sampling technique used total sampling, totaling 40 pregnant women in the Kutamendala Community Health Center Working Area, Brebes Regency. Results: Of the 40 respondents before the warm compress was applied, it was found that 30 respondents (75%) experienced mild levels of lower back pain, while 10 respondents (25%) experienced moderate levels of lower back pain, and after doing this Warm compresses showed that 32 respondents (80%) did not complain of lower back pain, while 8 respondents (20%) experienced low back pain at a mild level. The results of the analysis using the Wilcoxon test showed p value = 0.000 < 0.05. Conclusion: There is an influence of warm compresses on the level of lower back pain in third trimester pregnant women